Thrust Vector Control within a Geometric Sphere, and the Use of Euler's Tips to Create Jet Technology - Yuri A. Sazonov; Mikhail A. Mokhov; Inna V. Gryaznova; Victoria V. Voronova; Khoren A. Tumanyan; Egor I. Konyushkov (Salehan Institute of Higher Education, 2023)
This study aims to study the issues of choosing promising directions for the development of jet technology with the creation of energy-conserving technologies. The purpose of this article is to study the issues of choosing promising directions for the development of jet technology with the creation of energy-saving. Methodological approaches have been developed for solving inventive problems within the framework of training modern designers-inventors. A new patentable jet unit has been developed and presented, which makes it possible to control the thrust vector within a complete geometric sphere (when the thrust vector is capable of deviating to any angle ranging from +180° to -180°). For the first time, demonstration versions of a nozzle apparatus capable of realizing such flow reversals through annular channels are shown. The results of computer modeling of nozzle devices are focused on energy, production, and processing of hydrocarbons when distributing energy flows at process facilities. The individual results of the ongoing work can also be used in other industries, for instance, in the creation of small-sized high-speed unmanned vehicles for search and rescue operations. Proposals have been prepared to improve the methodology for solving inventive problems as part of the development of Leonard Euler’s ideas. Doi: 10.28991/CEJ-2023-09-10-011 Full Text: PDF